2022
DOI: 10.3389/fgene.2022.905518
|View full text |Cite
|
Sign up to set email alerts
|

A Cuproptosis-Related Gene Model For Predicting the Prognosis of Clear Cell Renal Cell Carcinoma

Abstract: Despite advances in its treatment, patients diagnosed with clear cell renal cell carcinoma (ccRCC) have a poor prognosis. The mechanism of cuproptosis has been found to differ from other mechanisms that regulate cell death, including apoptosis, iron poisoning, pyrophosphate poisoning, and necrosis. Cuproptosis is an essential component in the regulation of a wide variety of biological processes, such as cell wall remodeling and oxidative stress responses. However, cuproptosis-related genes’ expression in ccRCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Survivability studies showed that patients in the lower-than-normal risk category had a considerably better prognosis. Mei et al (2022) As demonstrated in the scatter graphs, the risk score was positively linked with B cells, M1 Macrophages, and CD4 memory activated T cells. We identified a substantial association between the majority of immune cells and three genes, including APEH and M0 macrophages, CLYBL and M2 macrophages, and ZNF844 and CD4 memory resting T cells.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Survivability studies showed that patients in the lower-than-normal risk category had a considerably better prognosis. Mei et al (2022) As demonstrated in the scatter graphs, the risk score was positively linked with B cells, M1 Macrophages, and CD4 memory activated T cells. We identified a substantial association between the majority of immune cells and three genes, including APEH and M0 macrophages, CLYBL and M2 macrophages, and ZNF844 and CD4 memory resting T cells.…”
Section: Discussionmentioning
confidence: 84%
“…Survivability studies showed that patients in the lower-than-normal risk category had a considerably better prognosis. Mei et al (2022) constructed a cuproptosis-related signature that was used to classify clear cell renal cell carcinoma patients into distinct risk clusters, with low-risk patients having a much better prognosis. Because the risk score is inconvenient to apply in practice, we created a nomogram that combines the risk score with clinicopathological variables to estimate patient survival time.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous past studies have identi ed the importance of cuproptosis-related genes in the ccRCC immune microenvironment and can predict OS in patients with ccRCC [49,50]. Chen's and Zhang's study showed that high expression of FDX1 was associated with a better prognosis of renal clear cell carcinoma and could be used as a potential prognostic indicator and therapeutic target for ccRCC [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the risk score distribution, survival status, and expression of CRGs from the signatures are shown in the TCGA training cohort, TCGA validation cohort, and E-MTAB validation cohort (Figures 6E, S2E, S2F). Also, as shown in Figure S3, we compared our signature with previously published signatures in the TCGA dataset, and the results showed that our signature had better predictive performance, especially for 5-year survival (23,24).…”
Section: Construction and Validation Of The Prognostic Signature Base...mentioning
confidence: 93%